In-vitro and In-vivo Fungicidal Evaluation against False Smut (Ustilaginoidea virens) of Rice - Ravali, Somshetty; Basha, S. Ameer; Babu, T. Kiran; Mohan, Y. Chandra; Pushpavalli, S. N. C. V. L.; Naik, Banoth Balaji (International Journal of Economic Plants, 2024)
The study was undertaken at two locations during kharif (June to October, 2021), at College Farm, College of Agriculture, Rajendranagar, Hyderabad, and Regional Sugar Cane and Rice Research Station, Rudrur, Nizamabad, to find out the most effective crop stage for managing false smut of rice through fungicide spraying. Our study evaluated three fungicides viz., propiconazole 25 EC, carbendazim 50% WP, and tebuconazole 50%+trifloxystrobin 25% w/w WG (75 WG) against false smut disease of rice under in vitro and field condition. Under in vitro, U. virens showed greater sensitive to tebuconazole+trifloxystrobin, with complete mycelial growth inhibition at minimum concentration (0.25 µg ml-1), followed by propiconazole (1 µg ml-1) and carbendazim (2.5 µg ml-1). Under field management, fungicides propiconazole 25 EC @ 1 ml l-1, carbendazim 50% WP @ 1 g l-1, and tebuconazole 50%+trifloxystrobin 25% w/w WG (75 WG) @ 0.8 g l-1 were sprayed at different crop growth stages (10% panicle emergence, 50% panicle emergence and a combination of both crop stages). The results indicated that two sprays of fungicides, first at 10% panicle emergence and another at 50% panicle emergence were more effective, followed by a single spray at 10% panicle emergence and 50% panicle emergence. Among the three fungicides, tebuconazole 50%+trifloxystrobin 25% w/w WG (75 WG) at 0.8 g l-1 was highly effective in reducing the false smut disease intensity and increasing the yield compared to control.